Integrin‐Targeted Cyclic Forces Accelerate Neural Tube‐Like Rosette Formation from Human Embryonic Stem Cells. Issue 10 (21st August 2019) - Topal, Tuğba; Fan, Zhenzhen; Deng, Laura Y.; Krebsbach, Paul H.; Deng, Cheri X.
Abstract: Mechanical forces play important roles in human embryonic stem cell (hESC) differentiation. To investigate the impact of dynamic mechanical forces on neural induction of hESCs, this study employs acoustic tweezing cytometry (ATC) to apply cyclic forces/strains to hESCs by actuating integrin‐bound microbubbles using ultrasound pulses. Accelerated neural induction of hESCs is demonstrated as the result of combined action of ATC and neural induction medium (NIM). Specifically, application of ATC for 30 min followed by culture in NIM upregulates neuroecdoderm markers Pax6 and Sox1 as early as 6 h after ATC, and induces neural tube‐like rosette formation at 48 h after ATC. In contrast, no changes are observed in hESCs cultured in NIM without ATC treatment. In the absence of NIM, ATC application decreases Oct4, but does not increase Pax6 and Sox1 expression, nor does it induce neural rossette formation. The effects of ATC are abolished by inhibition of FAK, myosin activity, and RhoA/ROCK signaling. Taken together, the results reveal a synergistic action of ATC and NIM as an integrated mechanobiology mechanism that requires both integrin‐targeted cyclic forces and chemical factors for accelerated neural induction of hESCs. Abstract : Acoustic tweezing cytometry (ATC) applies integrin‐targeted cyclic forces/strains to human embryonic stem cells (hESCs). Dependent on FAK, myosin activity, and RhoA/ROCK signaling, synergistic action of ATC for 30 min and neural induction medium greatly accelerates neural induction of hESCs, resulting in upregulated neuroecdoderm markers Pax6 and Sox1 by 6 h and neural tube‐like rosette formation at 48 h.